2017
DOI: 10.1007/s11356-017-9278-9
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous adsorption of Remazol brilliant blue and Disperse orange dyes on red mud and isotherms for the mixed dye system

Abstract: The paper presents the adsorption of Remazol brilliant blue (RBB) and Disperse orange 25 (DO25) dyes from aqueous solution of the mixture of dyes onto concentrated sulphuric acid-treated red mud (ATRM). First-order derivative spectrophotometric method was developed for the analysis of RBB and DO25 in mixed dye aqueous solution to overcome the limitations arising due to interference in the zero-order spectral method. The optimum conditions to maximize RBB adsorption favoured the adsorption of RBB, and those for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…The results confirmed that the TMPAA polymeric adsorbent has more affinity towards MG than MB [57]. Similar antagonistic analogous trends could be noticed also in the binary dyes solution of remazol brilliant blue (RBB) and disperse orange (DO) [58], methylene blue (MB) and methyl orange (MO) [59], and methyl orange (MO) and phenol [41].…”
Section: Figuresupporting
confidence: 61%
“…The results confirmed that the TMPAA polymeric adsorbent has more affinity towards MG than MB [57]. Similar antagonistic analogous trends could be noticed also in the binary dyes solution of remazol brilliant blue (RBB) and disperse orange (DO) [58], methylene blue (MB) and methyl orange (MO) [59], and methyl orange (MO) and phenol [41].…”
Section: Figuresupporting
confidence: 61%
“…Therefore the nickel molecules will block the surface sites for the phenol molecules to adsorb. It is also due to the fact that nickel was competing more for the active sites on the adsorbent [43][44]. Therefore, it can be observed that by increasing the nickel concentration the phenol capacity was decreasing and nickel was showing antagonistic effect on the phenol.…”
Section: The Interaction Effect Of the Pollutants In The Solution (Simentioning
confidence: 99%
“…The wastewater containing dye molecules must, then, be treated before the discharge in the natural medium in order to overcome their negative environmental impacts [7]. Industrial wastewater treatment involves various methods: advanced oxidation processes, precipitation/coagulation, and biological treatment [8,9]. Such processes have some drawbacks, including high-energy requirement, consumption of chemicals, high operational cost, and the possible generation of toxic materials [10].…”
Section: Introductionmentioning
confidence: 99%
“…Different types of modified and raw biosorbents such as rice husk, peat, pinus Sylvestris, red mud, sugarcane bagasse, etc. have been used for the removal of cationic dyes from aqueous solutions [9,[17][18][19][20][21]. Date pits, which are agro-industrial solid wastes largely produced in MENA countries, are promising candidates as effective adsorbents [4,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation